High-strength self-insulation saline-alkaline immature soil wall material and preparation method thereof
By freezing the saturated lignin fiber polymer to form an ice-lignin fiber polymer composite structure and adding it to the raw soil wall material, the problems of insufficient strength and insulation performance of existing raw soil wall materials are solved, and the effects of high strength, self-insulating and durability are achieved.
Patent Information
- Application Number
- CN202510116961.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-24
AI Technical Summary
The strength and insulation properties of existing raw soil wall materials need to be further improved, and the preparation materials are relatively complex.
By freezing the saturated lignin fiber polymer, an ice-lignin fiber polymer composite structure is formed, and it is added to the raw soil wall material as hard light particles. Combined with gelling materials and saline-alkali soil, the mixture and molding method is adopted under low temperature environment.
It effectively improves the mechanical properties and self-insulating properties of raw soil wall materials, reduces raw material costs, simplifies the preparation method, and improves the durability and seismic resistance of the material.
Smart Images

Figure CN119874273A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and more specifically to a high-strength self-insulating saline-alkaline raw soil wall material and a preparation method and application thereof. Background Art
[0002] Raw earth refers to the original earth material that has not been baked but only undergone simple compaction processing. The raw earth is pressed or poured into bricks of various sizes. Raw earth bricks can be used to build 1 to 3-story raw earth buildings. It is one of the most representative characteristics of human beings' transition from primitive to civilized.
[0003] The earliest and most common form of earth building is rammed earth building. Earth building is one of the oldest and most widely used building types. Since the formation of human society, earth has always been an important building material because of its wide distribution, convenient soil collection, economical and practical nature, and the fact that buildings built with earth are warm in winter and cool in summer, strong and durable. In addition, with the rapid development of the economy, people are generally concerned about the ecological and environmental crisis today, so we should follow the concept of sustainable development of the human living environment, re-examine the ancient building material "earth" from the social level of ecological civilization, and clearly realize that "earth" materials are green building materials with great development prospects.
[0004] Traditional earth buildings are made by adding straw to the soil and pressing it into bricks, which are then used to build walls and other building structures. The earth bricks prepared in this way have relatively low bending, shear and flexural strengths, and extremely low weather resistance, resulting in inherent deficiencies in earthquake resistance and a short service life.
[0005] Therefore, studying how to modify raw earth materials and improve the level of molding technology, enhance the strength of raw earth materials, and increase the service life of raw earth buildings has become the first problem that needs to be solved in raw earth material research.
[0006] There are many related studies on how to improve the comprehensive performance of raw soil materials. For example, the Chinese invention patent application with publication number CN102010173A discloses a method for preparing heat-insulating and crack-resistant raw soil bricks. This application provides a method for preparing heat-insulating and crack-resistant raw soil bricks that are low-cost, easy to produce, have good mechanical properties and durability, good crack resistance and thermal properties, and can be recycled and reused by effectively utilizing desulfurization ash from coal-fired power plants and agricultural solid waste crop straw. The compressive strength of the raw soil bricks prepared in this application can only reach 1.2Mpa.
[0007] For another example, the Chinese invention patent application with publication number CN111454019A discloses a method for preparing a rural high-strength raw soil material. The raw soil material components in this application include: 14-18 parts of crushed fine aggregate of abandoned buildings, 55-60 parts of plain soil, 1-2 parts of crushed plant fiber and 20-30 parts of cross-linked esterified modified mixed liquid. After mixing and stirring the above components, they are put into a mold for solidification to form raw soil blocks. Although the compressive strength of the raw soil material prepared in this application is significantly improved, and the compressive strength can reach 12MPa, the preparation process of the cross-linked esterified modified mixed liquid is too complicated.
[0008] For another example, the Chinese invention patent application with publication number CN109279857A discloses a high-performance raw earth brick and its preparation method. The raw materials in the application include raw earth, cement, slaked lime, water glass and polypropylene fiber, and also include styrene acrylic emulsion, calcium chloride and binder. The prepared blanks are pressed and formed under a pressure of 12MPa. The pressed bricks have a strength more than 2 times higher than traditional adobe bricks. Although the application can solve the problems of traditional raw earth bricks being non-waterproof and having poor durability, the raw earth bricks do not meet the requirements of self-insulation and do not have the function of absorbing seismic waves to resist earthquake damage. Summary of the invention
[0009] 1. Technical problems to be solved
[0010] The purpose of the present invention is to provide a high-strength self-insulating saline-alkali raw earth wall material and a preparation method thereof, so as to solve the problems that the strength and thermal insulation performance of the existing raw earth wall material need to be further improved, and the raw materials for its preparation are relatively complex. The wall material prepared by the present invention can not only effectively improve its mechanical properties and self-insulating performance, but also has low raw material cost and a simple and easy preparation method.
[0011] 2. Technical solutions adopted
[0012] In order to achieve the above object, the technical solution provided by the present invention is:
[0013] The first aspect of the present invention provides a high-strength self-insulating saline-alkali raw earth wall material, the wall material blank ingredients include cementitious material, raw earth, hard lightweight granular material and water, wherein the cementitious material, raw earth and water constitute the A component of the raw earth wall material blank, the hard lightweight granular material is the B component of the raw earth wall material blank, the hard lightweight granular material is an ice-lignin fiber polymer composite structure obtained by freezing saturated lignin fiber polymer particles, and is measured by volume fraction in a natural stacking state, and the volume fraction of component B in the raw earth wall material blank ingredients accounts for 10 to 30% of the sum of the volume fractions of component A and component B.
[0014] At present, in the high-pressure formed raw earth wall material, it is impossible to directly add lignin fiber polymer as a lightweight aggregate to play the role of heat insulation, sound insulation and earthquake resistance. The specific reasons are as follows: due to the elasticity of the lignin fiber polymer itself, after the compression molding is completed, it will quickly rebound inside the raw earth wall material blank to restore part of the deformation, which will destroy the compactness of the prepared blank and reduce its molding quality. The present invention modifies the lignin fiber polymer, that is, first saturating the lignin fiber polymer with water, then freezing it, freezing the saturated lignin fiber polymer, forming a frozen state of lignin fiber polymer, from an elastic lightweight granular object to a rigid ice-lignin fiber polymer composite structure of a hard lightweight granular object, which will not rebound after compression molding, thereby improving the structural strength and compactness of raw earth bricks. At the same time, the composite structure formed has a rigid body on the outside and a lignin fiber polymer on the inside, which avoids the direct accumulation of lignin fiber polymers during the pressing process. If there is a stacked floc structure in the raw earth wall material body, it will cause the local strength and density to decrease. In addition, after the pressing and forming, the raw earth wall material body has a slow heating process, which provides more time for the full hydration reaction of the cementitious raw materials in the wall material body. In addition, as the lignin particles thaw, the solid water therein is converted into liquid capillary water after forming, which is provided for the hydration reaction of the cementitious material, so that the hydration reaction is accelerated and complete, and the external water supply required for maintenance is reduced. Most importantly, as the raw earth body gradually heats up, the lignin fiber polymer does not deform and turns into a soft and lightweight aggregate in situ. This process will not cause stress damage to the raw earth body structure, thereby playing a role in sound insulation, heat insulation, and earthquake resistance in the wall material.
[0015] Furthermore, the volume fraction of component B in the blank ingredients of the raw earth wall material accounts for 10-25% of the sum of the volume fractions of component A and component B.
[0016] Furthermore, the interior of the lignin fiber aggregate is a solid core.
[0017] Furthermore, the particle size of the lignin fiber aggregate is 3 to 10 mm.
[0018] Furthermore, the air-dry density of the lignin fiber polymer is less than 0.9 g / cm 3 , thereby reducing the bulk density of the resulting green adobe body.
[0019] Furthermore, the lignin fiber polymer particles are solid rod-shaped crop straws, branches or crushed tree particles.
[0020] Furthermore, taking the sum of the masses of cementitious materials and raw soil as the whole, specifically: the mass of cementitious materials accounts for 20-50%, and the mass of raw soil accounts for 50-80%.
[0021] Furthermore, the amount of water added accounts for 10-20% of the sum of the mass of the cementitious material and the raw soil.
[0022] Furthermore, the air-dry density of the lignin fiber polymer is less than 0.7 g / cm 3 , thereby further reducing the bulk density of the resulting green adobe body.
[0023] Furthermore, the raw soil is saline-alkali raw soil, thereby further expanding the scope of raw soil material.
[0024] Furthermore, the water is saline water, thereby further increasing the source range of water in the raw materials of the wall material.
[0025] Furthermore, the cementitious material is any one of general-purpose cement, mineral-based cementitious material, and alkali-slag cement.
[0026] Furthermore, the cementitious material is alkali slag cement, and the alkaline activator in the alkali slag cement includes sodium hydroxide and sodium silicate. When the raw soil is saline-alkali raw soil and the water is saline-alkali water, the saline-alkali components in the two can also participate in the hydration activation process of the alkali slag cement, so that the amount of alkali added in the alkali slag cement is reduced, thereby reducing the material cost of the alkali slag cement.
[0027] Furthermore, the mass ratio of the sodium silicate to the alkaline excitation dose is 40% to 70%, and its modulus is 1 to 2.
[0028] Further, sodium hydroxide and sodium silicate are powdered raw materials or liquid raw materials. Further, sodium hydroxide and sodium silicate are powdered raw materials.
[0029] Furthermore, the mass ratio of the sodium hydroxide and sodium silicate converted into sodium oxide is 6-10% of the mass ratio of the alkali slag cement.
[0030] Furthermore, the slag powder in the alkali slag cement is S95 grade or above. Furthermore, the slag powder is S95 grade.
[0031] The second aspect of the present invention provides a method for preparing the above-mentioned high-strength self-insulating saline-alkali raw earth wall material, comprising: uniformly mixing raw materials including cementitious material, raw earth, hard and lightweight granular material and water to obtain a wall material blank; wherein the hard and lightweight granular material is modified by soaking the lignin fiber polymer in water to reach a saturated state, and then placing it in a low-temperature environment and cooling it to below zero degrees to obtain a hard and lightweight granular material.
[0032] Furthermore, raw materials including cementitious material, raw soil, hard light granular material and water are mixed uniformly to obtain wall material blanks, specifically comprising: mixing the cementitious material and raw soil uniformly and cooling them to obtain a powder mixture at 0°C to 5°C; and uniformly mixing the obtained powder mixture, water at 0 to 5°C and hard granular material according to a mix ratio, and storing them at 0 to 5°C for less than 0.5h to obtain wall material blanks.
[0033] In the process of preparing the wall material blank, the mixture is mixed at 0℃~5℃. By limiting the low temperature environment, the lignin fiber polymer can be better kept in a frozen state during the preparation process. During the pressing process, the hard lignin fiber can be effectively prevented from becoming a soft and lightweight aggregate, so as to prevent the thawing and becoming an elastic body, thereby destroying the compactness of the raw earth blank and reducing the molding quality. At the same time, the low temperature limit in the above preparation process can also prolong the time required for the hard lignin fiber in the blank to become a soft and lightweight aggregate, thereby further providing more time for the full reaction of the gelling raw materials.
[0034] Furthermore, after the lignin fiber aggregate is soaked in water to reach a saturated state, its surface is dried and then placed in a low temperature environment to be cooled to below zero degrees.
[0035] Furthermore, the wall material blank is pressed and formed at 5-20 MPa to obtain a wall material blank.
[0036] Furthermore, the obtained wall material blank is cured to obtain the wall material; the unconfined compressive strength of the obtained wall material reaches above 10 MPa.
[0037] Furthermore, the softening coefficient of the obtained wall material is 0.8 to 0.9.
[0038] Furthermore, the thermal conductivity of the obtained wall material is 0.1-0.6 W / km.
[0039] Furthermore, the bulk density of the obtained wall material is 1800-2100 kg / m 3 .
[0040] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0041] (1) The present invention freezes the soft granular lignin fiber polymer to form hard light particles, thereby converting the elastic lignin fiber polymer into a rigid ice-lignin fiber polymer composite structure. After compression molding, the rigid ice-lignin fiber polymer will not rebound quickly, thus overcoming the technical problem that it is impossible to add heat-insulating, sound-insulating, and shock-resistant lignin fiber polymer light aggregate particles to high-pressure molded wall materials. At the same time, by adding the soft light granular material to the wall material blank in the form of ice-lignin fiber polymer, the accumulation of flocs is avoided, thereby improving the density of the high-pressure molded raw soil material, thereby greatly improving the durability and weather resistance of the wall material.
[0042] (2) The present invention soaks the lignin fiber polymer in water to make it saturated with water, and then freezes it at below zero degrees to form a composite structure with higher strength. During the hydration of the gelling component in the wall material blank, the solid water in the lignin polymer is transformed into liquid capillary water after being formed, which can be provided for the hydration reaction of the gelling material, so that the hydration reaction is accelerated and complete. No external water is required under the sealed curing conditions, thus eliminating the need for a large amount of external water in the curing process.
[0043] (3) The present invention further makes the water in the raw soil wall material preferably saline-alkali water, and the raw soil used is preferably saline-alkali raw soil, further expanding the sources of available raw soil materials and water. At the same time, the saline-alkali raw soil and the saline-alkali components in the saline-alkali water can also participate in the hydration activation process of the alkali slag cementitious material, thereby reducing the amount of alkali added in the alkali slag cement and reducing the processing cost of the alkali slag cement.
[0044] (4) The raw earth wall material in the present invention can be either a solid brick or processed into a porous block. When processed into a block, its bulk density is greatly reduced, and it can also be used as a self-insulating wall material for the exterior and interior walls of high-rise buildings, further broadening the use of raw earth wall materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a flow chart for preparing the raw earth wall material in Example 1 of the present invention. DETAILED DESCRIPTION
[0046] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with embodiments.
[0047] The raw soil saline-alkali soil used in the following embodiments and comparative examples is described by taking silty saline-alkali soil as an example, which should not be understood as a limitation on the selection of raw soil in the technical solution of the present invention. The raw soil used may also be clay saline-alkali soil or ordinary raw soil.
[0048] The water used is explained by taking saline water as an example, which should not be understood as a limitation on the selection of water used in the technical solution of the present invention. The water used can be pure water or other domestic water.
[0049] The cementitious material used is described by taking alkali slag cement as an example, which should not be understood as a limitation on the selection of water used in the technical solution of the present invention. The cementitious material used can be general cement, mineral-based cementitious material, or alkali slag cement.
[0050] Example 1
[0051] The present invention provides a method for preparing a raw earth wall material, comprising:
[0052] (I) Raw material preparation: Based on the mass of cementitious material and raw soil as a whole, the mass of alkali slag cement accounts for 30%, and the mass of powdery saline-alkali raw soil accounts for 70%; the water used is saline-alkali water, and the amount of water used is 17% of the sum of the mass of cementitious material and raw soil. The mixture of cementitious material, raw soil and water is the blank component A of the raw soil wall material of this embodiment; the light granular material is the granules after crushing cotton straw, with a particle size of 3-4 mm and an air-dry density of 0.4 g / cm 3 The hard lightweight granular material is obtained by freezing the saturated lightweight granular material, which is the B component of the raw earth wall material of this embodiment; measured by the volume fraction in the natural stacking state, the volume fraction of the B component in the raw earth wall material blank is 10% of the sum of the volume fractions of the A component and the B component.
[0053] The alkaline activator in the alkali slag cement used is a composite of sodium hydroxide and sodium silicate, in which sodium silicate accounts for 50% and has a modulus of 1.5. The sodium hydroxide and sodium silicate in the alkali slag cement are converted into sodium oxide accounting for 6%. Sodium hydroxide and sodium silicate are powdered raw materials. The slag powder in the alkali slag cement used is S95 slag powder.
[0054] (ii) The modification treatment of the lightweight granules is as follows: the lightweight granules are soaked in water until they are saturated with water, and then the surfaces are air-dried, and then the granules are placed in a freezer and cooled to -10°C, so that the water in the lightweight granules is in a frozen state; that is, a composite structure of ice and lignin fibers is formed, so that the soft lightweight granules are transformed into hard lightweight granules at -10°C.
[0055] (III) The specific preparation process is as follows:
[0056] (1) Weighing the cementitious material and saline-alkali raw soil according to the proportion of the raw materials, and placing the mixed material in an environment of 0° C. for 1 h to 5 h until the temperature drops to 0 to 5° C., thereby obtaining a powdery mixture;
[0057] (2) according to the mixing ratio, the powdery mixture at 0 to 5°C is mixed with weighed water at 0°C and hard lightweight particles, and mixed evenly, and stored at 0 to 5°C for 10 minutes to obtain a wall material blank;
[0058] (3) The wall material blank prepared in step 2) is added into the material holding cavity of a uniaxial hydraulic forming mold for distribution, and then pressure-formed at a pressure of 20 MPa. After demolding, a high-strength self-insulating saline-alkali raw soil wall material blank is obtained. The size of the blank sample is a columnar body with a diameter of 30 mm and a thickness of 30 mm.
[0059] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil material product was obtained, with an unconfined compressive strength of 20MPa at 3 days, 28MPa at 7 days, 45MPa at 28 days, a softening coefficient of 0.9, and a bulk density of 2100kg / m 3 , thermal conductivity is 0.6W / km, and the strength and mass loss of the 28-day-old sample after 30 dry-wet cycles and freeze-thaw cycles is negligible. It has typical high-strength, self-insulation and weather-resistant functions.
[0060] Comparative Example 1
[0061] This comparative example provides a method for preparing a raw earth wall material, which differs from Example 1 in that: after the hard and lightweight granular material in a frozen state is thawed, the material is prepared according to the above-mentioned preparation process, and the remaining operations are basically the same.
[0062] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil material product was obtained, with an unconfined compressive strength of 0.05MPa at 3 days, 0.1MPa at 7 days, and 0.1MPa at 28 days. The softening coefficient was 0 (powdering in water), and the bulk density was 1800kg / m 3 , thermal conductivity is 0.6W / km, and the strength and mass losses of the 28-day-old sample are both 100% after 30 dry-wet cycles.
[0063] Comparative Example 2
[0064] This comparative example provides a method for preparing a raw earth wall material, which differs from Example 1 in that the pretreatment of the lightweight granular material is different, specifically, the lightweight granular material is not saturated with water, but directly frozen, and prepared according to the above preparation process, and the other operations are basically the same.
[0065] A large number of cracks appeared on the surface of the green body sample. The green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a saline-alkali raw soil material product was obtained. Its 3-day unconfined compressive strength was 0.05MPa, 7-day unconfined compressive strength was 0.1MPa, 28-day unconfined compressive strength was 0.1MPa, the softening coefficient was 0 (powdered when exposed to water), and the bulk density was 1800kg / m 3, thermal conductivity is 0.5W / km, and the strength and mass losses of the 28-day-old sample are both 100% after 30 dry-wet cycles and freeze-thaw cycles.
[0066] Comparative Example 3
[0067] This comparative example provides a method for preparing a raw earth wall material, which differs from Example 1 in that the selection of the lightweight granular material is different, specifically, the lightweight granular material is hollow wheat straw, and the other operations are basically the same.
[0068] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil material product was obtained, with an unconfined compressive strength of 5MPa at 3 days, 10MPa at 7 days, and 15MPa at 28 days. The softening coefficient was 0.7 and the bulk density was 2000kg / m 3 , thermal conductivity 0.5W / km, after 30 dry-wet cycles and freeze-thaw cycles of the 28-day-old sample, the strength and mass losses under the dry-wet cycle reached 10% and 1.5% respectively, and in the freeze-thaw cycle, the strength and mass losses reached 90% and 10% respectively, and the anti-freeze-thaw performance was not ideal.
[0069] Comparative Example 4
[0070] This comparative example provides a method for preparing a raw earth wall material, which differs from Example 1 in that the particle size of the lightweight granular material is different, specifically, the particle size of the lightweight granular material is 1 to 2 mm, and the other operations are basically the same.
[0071] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil material product was obtained. Due to the agglomeration of hard and light particles, the strength of the product was not high. The unconfined compressive strength was 2.5MPa at 3 days, 3.5MPa at 7 days, and 5.5MPa at 28 days. The softening coefficient was 0.6 and the bulk density was 2100kg / m 3 , thermal conductivity 1.05W / km, after 30 dry-wet cycles and freeze-thaw cycles of the 28-day-old sample, the product collapsed, and the strength and mass losses reached 100%.
[0072] Comparative Example 5
[0073] This comparative example provides a method for preparing a raw earth wall material, which differs from Example 1 in that the particle size of the lightweight granular material is different, specifically, the particle size of the lightweight granular material is 12 to 14 mm, and the remaining operations are basically the same.
[0074] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil material product was obtained, with an unconfined compressive strength of 5MPa at 3 days, 7.5MPa at 7 days, and 10MPa at 28 days. The softening coefficient was 0.8 and the bulk density was 2000kg / m 3 , thermal conductivity 0.8W / km, after 30 dry-wet cycles and freeze-thaw cycles, the strength and mass losses of the 28-day-old sample are negligible. Compared with Example 1, in addition to a more significant decrease in strength, it also has certain self-insulation and weather resistance functions.
[0075] Example 2
[0076] This embodiment provides a method for preparing a raw earth wall material, comprising:
[0077] (I) Raw material preparation: The mass of cementitious material and raw soil is 100%, of which the mass of alkali slag cement accounts for 40% and the mass of powdery saline-alkali raw soil accounts for 60%; the water used is saline-alkali water, of which the amount of water is 13% of the sum of the mass of cementitious material and raw soil. The mixture of cementitious material, raw soil and water is the blank component A of the raw soil wall material of this embodiment; the lightweight granular material is the particles of paulownia tree branches crushed, with a particle size of 3-5 mm and an air-dry density of 0.4 g / cm 3 The hard lightweight granular material is obtained by freezing the saturated lightweight granular material, which is the B component of the raw earth wall material of this embodiment; measured by the volume fraction in the natural stacking state, the volume fraction of the B component in the raw earth wall material blank is 20% of the sum of the volume fractions of the A component and the B component.
[0078] The alkaline activator in the alkali slag cement used is a composite of sodium hydroxide and sodium silicate, in which sodium silicate accounts for 60% of the composite activator, and the modulus is 2. The sodium hydroxide and sodium silicate in the alkali slag cement are converted into sodium oxide, which accounts for 10%. Sodium hydroxide and sodium silicate are powdered raw materials, and the slag powder in the alkali slag cement used is S95 slag powder.
[0079] (ii) The pretreatment of the lightweight particles is as follows: the lightweight particles are soaked in water until they are saturated with water, and then the surfaces are air-dried, and then placed in a freezer to be cooled to -15°C, so that the water in the lightweight particles is in a frozen state; that is, a composite structure of ice and lignin fibers is formed, so that the soft lightweight particles are transformed into hard lightweight particles at -15°C.
[0080] (III) The preparation process is as follows:
[0081] (1) Weighing a cementitious material and saline-alkali raw soil according to the proportion of raw materials, and placing the mixed material in an environment of 0° C. for 1 h to 5 h until the temperature thereof is 0 to 5° C., thereby obtaining a powdery mixture;
[0082] (2) according to the mixing ratio, the powdery mixture at 0 to 5°C is mixed with weighed water at 0°C and hard lightweight particles, and mixed evenly, and stored at 0 to 5°C for 10 minutes to obtain a wall material blank;
[0083] (3) The wall material blank prepared in step 2) is added into the material holding cavity of a uniaxial hydraulic forming mold for distribution, and then pressure-formed at a pressure of 15 MPa. After demolding, a high-strength self-insulating saline-alkali raw soil wall material blank is obtained. The size of the blank sample is a columnar body with a diameter of 100 mm and a thickness of 100 mm.
[0084] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil wall material product was obtained, with an unconfined compressive strength of 7.5MPa at 3 days, 10MPa at 7 days, 16MPa at 28 days, a softening coefficient of 0.85, and a bulk density of 1900kg / m 3 , thermal conductivity is 0.15W / km, and the strength and mass loss of the 28-day-old sample after 30 dry-wet cycles and freeze-thaw cycles is negligible. It has typical high-strength, self-insulation and weather-resistant functions.
[0085] Example 3
[0086] This embodiment provides a method for preparing a raw earth wall material, comprising:
[0087] (I) Raw material preparation: Based on the mass of cementitious material and raw soil as a whole, the mass of alkali slag cement accounts for 30%, and the mass of powdery saline-alkali raw soil accounts for 70%; the water used is saline-alkali water, and the amount of water used is 13% of the sum of the mass of cementitious material and raw soil. The mixture of cementitious material, raw soil and water is the blank component A of the raw soil wall material of this embodiment; the lightweight granular material is the particles of crushed poplar wood, with a particle size of 5 to 10 mm and an air-dry density of 0.6 g / cm 3 The hard lightweight granular material is obtained by freezing the saturated lightweight granular material, which is the B component of the raw earth wall material of this embodiment; measured by the volume fraction in the natural stacking state, the volume fraction of the B component in the raw earth wall material blank is 15% of the sum of the volume fractions of the A component and the B component.
[0088] The alkaline activator in the alkali slag cement used is a composite of sodium hydroxide and sodium silicate, in which sodium silicate accounts for 55% of the composite activator and has a modulus of 1.5. The sodium hydroxide and sodium silicate in the alkali slag cement are converted into sodium oxide, accounting for 8%. Sodium hydroxide and sodium silicate are powdered raw materials, and the slag powder in the alkali slag cement used is S95 slag powder.
[0089] (ii) The pretreatment of the lightweight particles is as follows: the lightweight particles are soaked in water until they are saturated with water, and then the surfaces are air-dried, and then placed in a freezer to be cooled to -15°C, so that the water in the lightweight particles is in a frozen state; that is, a composite structure of ice and lignin fibers is formed, so that the soft lightweight particles are transformed into hard lightweight particles at -15°C.
[0090] (III) The preparation process is as follows:
[0091] (1) Weighing the cementitious material and saline-alkali raw soil according to the proportion of the raw materials, and placing the mixed material in an environment of 0° C. for 1 h to 5 h until the temperature of the material is 0 to 5° C., thereby obtaining a powdery mixture;
[0092] (2) according to the mixing ratio, the powdery mixture at 0 to 5°C is mixed with weighed water at 0°C and hard lightweight particles, and mixed evenly, and stored at 0 to 5°C for 10 minutes to obtain a wall material blank;
[0093] (3) The wall material blank prepared in step 2) is added into the material holding cavity of a uniaxial hydraulic forming mold for distribution, and then pressure-formed at a pressure of 10 MPa. After demolding, a high-strength self-insulating saline-alkali raw soil wall material blank is obtained. The size of the blank sample is a columnar body with a diameter of 100 mm and a thickness of 100 mm.
[0094] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil wall material product was obtained, with an unconfined compressive strength of 10MPa at 3 days, 15MPa at 7 days, and 20MPa at 28 days. The softening coefficient was 0.9 and the bulk density was 2000kg / m 3 , thermal conductivity is 0.25W / km, and the strength and mass loss of the 28-day-old sample after 30 dry-wet cycles and freeze-thaw cycles is negligible. It has typical high-strength, self-insulation and weather-resistant functions.
[0095] Example 4
[0096] This embodiment provides a method for preparing a raw soil brick, comprising:
[0097] (I) Raw material preparation: Based on the mass of cementitious material and raw soil as a whole, the mass of alkali slag cement accounts for 30%, and the mass of powdery saline-alkali raw soil accounts for 70%; the water used is saline-alkali water, in which the amount of water is 13% of the sum of the mass of cementitious material and raw soil. The mixture of cementitious material, raw soil and water is the blank component A of the raw soil wall material of this embodiment; the light granular material is the crushed particles of willow wood waste, with a particle size of 3 to 5 mm and an air-dry density of 0.4 g / cm 3The hard lightweight granular material is obtained by freezing the saturated lightweight granular material, which is the B component of the raw earth wall material of this embodiment; measured by the volume fraction in the natural stacking state, the volume fraction of the B component in the raw earth wall material blank is 25% of the sum of the volume fractions of the A component and the B component.
[0098] The alkaline activator in the alkali slag cement used is a composite of sodium hydroxide and sodium silicate, in which sodium silicate accounts for 55% of the composite activator and has a modulus of 1.5. The sodium hydroxide and sodium silicate in the alkali slag cement are converted into sodium oxide, accounting for 8%. Sodium hydroxide and sodium silicate are powdered raw materials, and the slag powder in the alkali slag cement used is S95 slag powder.
[0099] (ii) The pretreatment of the lightweight particles is as follows: the lightweight particles are soaked in water until they are saturated with water, and then the surfaces are air-dried, and then placed in a freezer to be cooled to -15°C, so that the water in the lightweight particles is in a frozen state; that is, a composite structure of ice and lignin fibers is formed, so that the soft lightweight particles are transformed into hard lightweight particles at -15°C.
[0100] (III) The specific preparation process is as follows:
[0101] (1) Weighing the cementitious material and saline-alkali raw soil according to the proportion of the raw materials, and placing the mixed material in an environment of 0° C. for 1 h to 5 h until the temperature of the material is 0 to 5° C., thereby obtaining a powdery mixture;
[0102] (2) according to the mixing ratio, the powdery mixture at 0 to 5°C is mixed with weighed water at 0°C and hard lightweight particles, and mixed evenly, and stored at 0 to 5°C for 10 minutes to obtain a wall material blank;
[0103] (3) The wall material blank prepared in step 2) is added into the material holding cavity of a uniaxial hydraulic forming mold for distribution, and then pressure-formed at a pressure of 5 MPa. After demolding, a high-strength self-insulating saline-alkali raw soil wall material blank is obtained. The size of the blank sample is a columnar body with a diameter of 100 mm and a thickness of 100 mm.
[0104] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil wall material product was obtained, with an unconfined compressive strength of 6MPa at 3 days, 8MPa at 7 days, 13MPa at 28 days, a softening coefficient of 0.85, and a bulk density of 1850kg / m 3 , thermal conductivity is 0.1W / km, and the strength and mass loss of the 28-day-old sample after 30 dry-wet cycles and freeze-thaw cycles is negligible. It has typical high-strength, self-insulation and weather-resistant functions.
[0105] Example 5
[0106] This embodiment provides a method for preparing a raw earth wall material, comprising:
[0107] (I) Raw material preparation: Based on the mass of cementitious material and raw soil as a whole, the mass of alkali slag cement accounts for 30%, and the mass of powdery saline-alkali raw soil accounts for 70%; the water used is saline-alkali water, in which the amount of water is 13% of the sum of the mass of cementitious material and raw soil. The mixture of cementitious material, raw soil and water is the blank component A of the raw soil wall material of this embodiment; the light granular material is the particles of crushed hard pine wood waste, with a particle size of 3 to 5 mm and an air-dry density of 0.7 g / cm 3 The hard lightweight granular material is obtained by freezing the saturated lightweight granular material, which is the B component of the raw earth wall material of this embodiment; measured by the volume fraction in the natural stacking state, the volume fraction of the B component in the raw earth wall material is 30% of the sum of the volume fractions of the A component and the B component.
[0108] The alkaline activator in the alkali slag cement used is a composite of sodium hydroxide and sodium silicate, in which sodium silicate accounts for 55% of the composite activator and has a modulus of 1.5. The sodium hydroxide and sodium silicate in the alkali slag cement are converted into sodium oxide, accounting for 8%. Sodium hydroxide and sodium silicate are powdered raw materials, and the slag powder in the alkali slag cement used is S95 slag powder.
[0109] (ii) The pretreatment of the lightweight particles is as follows: the lightweight particles are soaked in water until they are saturated with water, and then the surfaces are air-dried, and then placed in a freezer to be cooled to -15°C, so that the water in the lightweight particles is in a frozen state; that is, a composite structure of ice and lignin fibers is formed, so that the soft lightweight particles are transformed into hard lightweight particles at -15°C.
[0110] (III) The specific preparation process is as follows:
[0111] (1) Weighing the cementitious material and saline-alkali raw soil according to the proportion of the raw materials, and placing the mixed material in an environment of 0° C. for 1 h to 5 h until the temperature of the material is 0 to 5° C., thereby obtaining a powdery mixture;
[0112] (2) according to the mixing ratio, the powdery mixture at 0 to 5°C is mixed with weighed water at 0°C and hard lightweight particles, and mixed evenly, and stored at 0 to 5°C for 10 minutes to obtain a wall material blank;
[0113] (3) The wall material blank prepared in step 2) is added into the material holding cavity of a uniaxial hydraulic forming mold for distribution, and then pressure-formed at a pressure of 20 MPa. After demolding, a high-strength self-insulating saline-alkali raw soil wall material blank is obtained. The size of the blank sample is a columnar body with a diameter of 100 mm and a thickness of 100 mm.
[0114] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil wall material product was obtained, with an unconfined compressive strength of 5MPa at 3 days, 7.5MPa at 7 days, 10MPa at 28 days, a softening coefficient of 0.85, and a bulk density of 1800kg / m 3 , thermal conductivity 0.1W / km, after 30 dry-wet cycles and freeze-thaw cycles, the strength and mass loss of the 28-day-old sample can be ignored, and it has typical high-strength, self-insulation and weather resistance functions.
[0115] Example 6
[0116] This embodiment provides a method for preparing a raw earth wall material, comprising:
[0117] (I) Raw material preparation: Based on the mass of cementitious material and raw soil as a whole, the mass of alkali slag cement accounts for 20%, and the mass of powdery saline-alkali raw soil accounts for 80%; the water used is saline-alkali water, wherein the amount of water used is 15% of the sum of the mass of cementitious material and raw soil, and the mixture of cementitious material, raw soil and water is the blank component A of the raw soil wall material of this embodiment; the light granular material is the granules after crushing cotton straw, the particle size is 5-6 mm, and the air-dry density is 0.4 g / cm 3 The hard lightweight granular material is obtained by freezing the saturated lightweight granular material, which is the B component of the raw earth wall material of this embodiment; measured by the volume fraction in the natural stacking state, the volume fraction of the B component in the raw earth wall material blank is 25% of the sum of the volume fractions of the A component and the B component.
[0118] The alkaline activator in the alkali slag cement used is a composite of sodium hydroxide and sodium silicate, in which sodium silicate accounts for 60% of the composite activator and has a modulus of 1.5. The sodium hydroxide and sodium silicate in the alkali slag cement are converted into sodium oxide accounting for 10%. Sodium hydroxide and sodium silicate are powdered raw materials, and the slag powder in the alkali slag cement used is S95 slag powder.
[0119] (ii) The pretreatment of the lightweight particles is as follows: the lightweight particles are soaked in water until they are saturated with water, and then the surfaces are air-dried, and then placed in a freezer to be cooled to -18°C, so that the water in the lightweight particles is in a frozen state; that is, a composite structure of ice and lignin fibers is formed, so that the soft lightweight particles are transformed into hard lightweight particles at -18°C.
[0120] (III) The specific preparation process is as follows:
[0121] (1) Weighing the cementitious material and saline-alkali raw soil according to the proportion of the raw materials, and placing the mixed material in an environment of 0° C. for 1 h to 5 h until the temperature of the material is 0 to 5° C., thereby obtaining a powdery mixture;
[0122] (2) according to the mixing ratio, the powdery mixture at 0 to 5°C is mixed with the weighed water at 0°C and the hard and light particles, and mixed evenly, and stored at 0 to 5°C for 15 minutes to obtain a wall material blank;
[0123] (3) The wall material blank prepared in step 2) is added into the material holding cavity of a uniaxial hydraulic forming mold for distribution, and then pressure-formed at a pressure of 20 MPa. After demolding, a high-strength self-insulating saline-alkali raw soil wall material blank is obtained. The size of the blank sample is a columnar body with a diameter of 100 mm and a thickness of 100 mm.
[0124] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil wall material product was obtained, with an unconfined compressive strength of 5.5 MPa at 3 days, 7.5 MPa at 7 days, and 12 MPa at 28 days. The softening coefficient was 0.85 and the bulk density was 1830 kg / m 3 , thermal conductivity is 0.1W / km, and the strength and mass loss of the 28-day-old sample after 30 dry-wet cycles and freeze-thaw cycles is negligible. It has typical high-strength, self-insulation and weather-resistant functions.
[0125] Example 7
[0126] This embodiment provides a method for preparing a raw earth wall material, comprising:
[0127] (I) Raw material preparation: Based on the mass of cementitious material and raw soil as a whole, the mass of alkali slag cement accounts for 50%, and the mass of powdery saline-alkali raw soil accounts for 50%; the water used is saline-alkali water, wherein the amount of water used is 15% of the sum of the mass of cementitious material and raw soil, and the mixture of cementitious material, raw soil and water is the blank component A of the raw soil wall material of this embodiment; the light granular material is the granules after crushing cotton straw, the particle size is 6-7 mm, and the air-dry density is 0.4 g / cm 3 The hard lightweight granular material is obtained by freezing the saturated lightweight granular material, which is the B component of the raw earth wall material of this embodiment; measured by the volume fraction in the natural stacking state, the volume fraction of the B component in the raw earth wall material blank is 25% of the sum of the volume fractions of the A component and the B component.
[0128] The alkaline activator in the alkali slag cement used is a composite of sodium hydroxide and sodium silicate, in which sodium silicate accounts for 55% of the composite activator and has a modulus of 1.5. The sodium hydroxide and sodium silicate in the alkali slag cement are converted into sodium oxide, accounting for 8%. Sodium hydroxide and sodium silicate are powdered raw materials, and the slag powder in the alkali slag cement used is S95 slag powder.
[0129] (ii) The pretreatment of the lightweight particles is as follows: the lightweight particles are soaked in water until they are saturated with water, and then the surfaces are air-dried, and then placed in a freezer to be cooled to -18°C, so that the water in the lightweight particles is in a frozen state; that is, a composite structure of ice and lignin fibers is formed, so that the soft lightweight particles are transformed into hard lightweight particles at -18°C.
[0130] (III) The specific preparation process is as follows:
[0131] (1) Weighing the cementitious material and saline-alkali raw soil according to the proportion of the raw materials, and placing the mixed material in an environment of 0° C. for 1 h to 5 h until the temperature of the material is 0 to 5° C., thereby obtaining a powdery mixture;
[0132] (2) according to the mixing ratio, the powdery mixture at 0 to 5°C is mixed with the weighed water at 0°C and the hard and light particles, and mixed evenly, and stored at 0 to 5°C for 20 minutes to obtain a wall material blank;
[0133] (3) The wall material blank prepared in step 2) is added into the material holding cavity of a uniaxial hydraulic forming mold for distribution, and then pressure-formed at a pressure of 20 MPa. After demolding, a high-strength self-insulating saline-alkali raw soil wall material blank is obtained. The size of the blank sample is a columnar body with a diameter of 100 mm and a thickness of 100 mm.
[0134] The obtained green body sample was cured at room temperature and moisturizing conditions. After 28 days of curing, a high-strength self-insulating saline-alkali raw soil wall material product was obtained, with an unconfined compressive strength of 7MPa at 3 days, 8MPa at 7 days, and 13MPa at 28 days. The softening coefficient was 0.88 and the bulk density was 1800kg / m 3 , thermal conductivity is 0.1W / km, and the strength and mass loss of the 28-day-old sample after 30 dry-wet cycles and freeze-thaw cycles is negligible. It has typical high-strength, self-insulation and weather-resistant functions.
Claims
1. A high-strength self-insulating saline-alkaline raw soil wall material, characterized in that: The wall material blank ingredients include cementitious material, raw soil, hard light granular material and water, wherein the cementitious material, raw soil and water constitute the A component of the raw soil wall material blank, the hard light granular material is the B component of the raw soil wall material blank, the hard light granular material is an ice-lignin fiber polymer composite structure obtained by freezing saturated lignin fiber polymer particles, and is measured by volume fraction in a natural stacking state, and the volume fraction of the B component in the raw soil wall material blank ingredients accounts for 10 to 30% of the sum of the volume fractions of the A component and the B component.
2. The high-strength self-insulating saline-alkali raw soil wall material according to claim 1 is characterized in that: The volume fraction of component B in the blank ingredients of the raw earth wall material is 10-25% of the sum of the volume fractions of component A and component B; and / or the interior of the lignin fiber polymer is a solid core; and / or the particle size of the lignin fiber aggregate is 3 to 10 mm; And / or the air-dry density of the lignin fiber polymer is less than 0.9 g / cm 3 ; And / or the lignin fiber polymer particles are solid-core rod-shaped crop straws, branches or crushed tree particles; The sum of the mass of cementitious materials and raw soil is taken as the whole, specifically: the mass of cementitious materials accounts for 20-50%, and the mass of raw soil accounts for 50-80%; The amount of water added is 10-20% of the sum of the mass of cementitious materials and raw soil.
3. The high-strength self-insulating saline-alkali raw soil wall material according to claim 1, characterized in that: The air-dry density of the lignin fiber polymer is less than 0.7 g / cm 3 .
4. The high-strength self-insulating saline-alkaline raw soil wall material according to claim 1, characterized in that: The raw soil is saline-alkali raw soil; and / or the water is saline water; And / or the cementitious material is any one of general-purpose cement, mineral-based cementitious material, and alkali-slag cement.
5. The high-strength self-insulating saline-alkaline raw soil wall material according to claim 1, characterized in that: The cementitious material is alkali slag cement, and the alkaline activator in the alkali slag cement includes sodium hydroxide and sodium silicate.
6. The high-strength self-insulating saline-alkali raw soil wall material according to claim 5, characterized in that: The mass ratio of the sodium silicate to the alkaline excitation amount is 40-70%, and its modulus is 1-2; And / or sodium hydroxide and sodium silicate are powdered raw materials or liquid raw materials; And / or the mass ratio of the sodium hydroxide and sodium silicate converted into sodium oxide is 6-10% of the mass ratio of the alkali slag cement; And / or the slag powder in the alkali slag cement is slag powder of S95 level or above.
7. A method for preparing a high-strength self-insulating saline-alkaline raw soil wall material according to any one of claims 1 to 6, characterized in that: include: The raw materials including cementitious material, raw soil, hard light granular material and water are mixed evenly to obtain wall material blanks; wherein the modification method of the hard light granular material is: immersing the lignin fiber polymer in water to reach a saturated state and then placing it in a low temperature environment and cooling it to below zero degrees to obtain the hard light granular material.
8. The method for preparing the high-strength self-insulating saline-alkaline raw soil wall material according to claim 7, characterized in that: The raw materials including the cementitious material, the raw soil, the hard light granular material and the water are mixed uniformly to obtain the wall material blank, which specifically includes: The cementitious material and the raw soil are mixed evenly and cooled to obtain a powdery mixture at a temperature of 0°C to 5°C; The obtained powdery mixture, water at 0-5°C and hard granular materials are uniformly mixed according to the mixing ratio, and stored at 0-5°C for less than 0.5h to obtain a wall material blank. And / or drying the surface of the lignin fiber aggregate after soaking it in water to reach a saturated state, and then cooling it to below zero degrees.
9. The method for preparing the high-strength self-insulating saline-alkali raw soil wall material according to claim 7 or 8, characterized in that: The wall material blank is pressed and formed at 5-20 MPa to obtain a wall material blank.
10. The method for preparing the high-strength self-insulating saline-alkaline raw soil wall material according to claim 9, characterized in that: The obtained wall material blank is cured to obtain a wall material; the unconfined compressive strength of the wall material reaches more than 10MPa; and / or the softening coefficient of the wall material is 0.8 to 0.9; and / or the thermal conductivity of the wall material is 0.1 to 0.6 W / km; And / or the bulk density of the wall material is 1800-2100 kg / m 3 .
Citation Information
Patent Citations
Method for preparing heat insulation anti-cracking raw soil bricks
CN102010173A
High-performance immature-soil brick and preparation method thereof
CN109279857A
Preparation method of rural high-strength raw soil material
CN111454019A
Composite light wall board and production method thereof
CN102936939A
Plant fiber lightweight aggregate-raw soil thermal insulation block and preparation method thereof
CN104386978A